Genealogies of Fiction : Women Warriors and the Medieval Imagination in the "Orlando furioso" - Stoppino, Eleonora (Book collections on Project MUSE., 2012)
"Genealogies of Fiction is a study of gender, dynastic politics, and intertextuality in medieval and Renaissance chivalric epic, focused on Ludovico Ariosto's Orlando furioso. Relying on the direct study of manuscripts and incunabula, this project challenges the fixed distinction between medieval and early modern texts and reclaims medieval popular epic as a key source for the Furioso. Tracing the formation of the character of the warrior woman, from the amazon to Bradamante, the book analyzes the process of gender construction in early modern Italy. By reading the tension between the representations of women as fighters, lovers, and mothers, this study shows how the warrior woman is a symbolic center for the construction of legitimacy in the complex web of fears and expectations of the Northern Italian Renaissance court"--